General evaluation score for predicting the development of hepatocellular carcinoma in patients with advanced liver fibrosis associated with hepatitis C virus genotype 1 or 2 after direct‐acting antiviral therapy. Issue 7 (8th June 2022) - Tada, Toshifumi; Kurosaki, Masayuki; Tamaki, Nobuharu; Yasui, Yutaka; Mori, Nami; Tsuji, Keiji; Hasebe, Chitomi; Joko, Koji; Akahane, Takehiro; Furuta, Koichiro; Kobashi, Haruhiko; Fujii, Hideki; et al.
Abstract: Background and Aim: To validate a composite predictive model for hepatocellular carcinoma (HCC) development in patients with advanced liver fibrosis associated with chronic hepatitis C virus (HCV) who have received direct‐acting antiviral (DAA) therapy and achieved sustained virologic response (SVR). Methods: This study included 1258 patients with advanced liver fibrosis associated with HCV genotype 1, 2, or both. General evaluation score (GES), which is based on sex, age, fibrosis stage, albumin, and α‐fetoprotein, was used as a composite predictive model. Results: There were 645 (51.3%) patients in the low‐risk group, 228 (18.1%) in the intermediate‐risk group, and 385 (30.6%) in the high‐risk group based on GES categories. The 12‐, 36‐, and 60‐month cumulative incidence of HCC was 0.7%, 5.3%, and 13.0%, respectively. Multivariable analysis with Cox proportional hazards models showed that male sex (hazard ratio [HR], 1.863; 95% confidence interval [CI], 1.204–2.883), F4 fibrosis stage (HR, 3.199; 95% CI, 1.696–6.036), and albumin (HR, 0.489; 95% CI, 0.288–0.828) are independently associated with HCC development. The incidence of HCC differed significantly by GES‐based risk category ( P < 0.001). Cox proportional hazards models showed that, with the low‐risk group as the referent, the HR for HCC development was 1.875 (95% CI, 1.000–3.514) in the intermediate‐risk group and 2.819 (95% CI, 1.716–4.630) in the high‐risk group. GES had better predictive ability for HCC development than fibrosis‐4 index according to time‐dependent receiver operating characteristic analysis. Conclusion: GES is useful for predicting HCC development in patients with advanced liver fibrosis after SVR. Abstract : To validate the utility of the general evaluation score (GES) for predicting the development of hepatocellular carcinoma (HCC) in patients with advanced liver fibrosis associated with hepatitis C virus genotype 1 or 2 who have received direct‐acting antiviral. The incidence of HCC differed significantly by GES‐based risk groups in this patient population. GES had higher predictive power for HCC development than FIB‐4 index according to time‐dependent receiver operating characteristic analysis.